Land, liberation and democracy: the life and work of Lionel Cliffe. (22nd August 2016) - Lawrence, Peter
ABSTRACT: This paper is a revised version, for this issue, of the keynote address to the Colloquium in Cape Town in honour of Lionel Cliffe. It maps out the key features of Lionel's life and his work starting in Tanzania in 1961, where through his long period of teaching, research and engagement, he formed much of what became his approach to the analysis of African social formations and appropriate policies for development and change. His founding role in this journal, his periods of further work in Zambia, the Horn, and then Southern Africa, are viewed through the three themes of the title. They add up to a major contribution to both theory and practice that has continuing relevance to answering the question he often put: what is to be done?